Revitalisasi Agrikultur untuk Pertumbuhan Ekonomi: Perspektif Ekonomi Islam - Suharno Suharno (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
Indonesia is an agricultural country that has natural wealth in the form of fertile land. The land area in Indonesia is 36.74 million m2. As an agricultural country, Indonesians consume rice as a staple food. If calculated the level of rice consumption of Indonesian people is 154 kg per person per year. These conditions are commonplace, given the vast land in Indonesia. But in reality, to meet the rice needs of the Indonesian people, the government must import rice from various countries. In accordance with BPS data in 2015, Indonesia imported 861 thousand tons of rice. A very sad fact given the natural wealth we have. This study aims to revitalize Indonesian agriculture from an Islamic economic perspective. The study was conducted through two stages. First, optimizing the mandate of natural resources by prospering the earth and the need for mindset changes among young people about agriculture. Second, optimizing the management of agricultural zakat to increase farmers' capital. With the pattern of agricultural zakat being productive. Keywords: agricultural revitalization, productive zakat, economic growth